KOMPETENSI GURU MILITER DI RESIMEN INDUK KODAM VII/WIRABUANA (WRB) - Yusa Djuyandi; Arman Aris Sallo (Department of Sociology, Faculty of Social and Political Science, Universitas Padjadjaran, 2021)
Despite the existence and role of military teachers is important, but military teacher competence in Rindam VII / Wrb still beyond hope, yet suitability military teacher competence can lead to decreased quality of learner outcomes soldiers. To analyze the question of the competence of military teachers, researchers used a competence theory as an analytical tool. The method used in this study is a qualitative method, with the source of data derived from the literature and field studies (observation and interviews). Results of research on military teacher competence from the aspect of capabilities, knowledge and skills of military teachers still indicate a weakness where there are still some military teachers who do not have the qualifications and specialization as a military teacher. The bottleneck in improving military teacher competence, besides due to lack of educational facilities, also caused by low skills and motivation of some military teachers. From research conducted can be concluded that the competence Gumil in Rindam VII / Wrb still low, it affects the students that generated by Rindam VII / Wrb.